Structural Analysis and Renovation Design of Ageing Sewers. Design Theories and Case Studies - Yoshifumi, Takahashi (De Gruyter, 2016)
In Japan, as a large number of sewer lines approach and exceed their design service life, rehabilitation of these ageing sewers to ensure their safe operation and upgrade their functions gains urgence. In this pioneering work, Z. Shi, M. Nakano and Y. Takahashi present a systematic treatment of structural analysis and renovation design of ageing sewers as semi-composite pipes, including testing and construction guidelines. The concept of a semi-composite pipe and the application of fracture mechanics of concrete in numerical modelling are the two distinctive features of the established design theories, which have been employed for sewer renovation in Japan for more than 20 years, with the total length of renovation construction now exceeding 700 km. The leading authors have engaged in designing the renovation of ageing sewers since the mid 1990s, and the book will become a valuable reference work for sewer engineers worldwide, and academics and students in civil, urban and architectural engineering departments.